Histological Comparison of Honey with Formocresol in Partial Pulpotomy of Deciduous Molars (Medical Forum Monthly, 2021)
Objective: The objective of this study is to histologically evaluate the repair of pulpal tissue after partial pulpotomy by covering the pulp tissue with Formocresol or with Honey.Study Design: Randamoized controlled trial study.Place and Duration of Study: The study was a conducted in de’Montmorency College of Dentistry, Lahore in six months time from January 2018 to June 2018.Materials and Methods: Since the study population were minors, a written informed consent was taken from the parent/gaurdian after explaining the procedure to them. 140 deciduous molars were randomly assigned for partial pulpotomy with Honey or Formocresol. The treated teeth were radiographically and clinically examined seven days and 60 days prior to extraction. The extracted teeth were then evaluated histologically for pulpal response.Results: Honey is more effective in a long term therapy. Results prove that Formocresol gave instant relief but was effective more only in short term treatments.Conclusion: There is prospective of honey as an active biologic pulp dressing agent without affecting the normal function. It is a natural harmless material with a long shelf-life that can replace formocresol.